Stalingrad Battle in Mirror of Regional British Press (Western Post Newspaper, 1942—1943) - M. Öztürk; Yu. G. Kokorina; M. M. Vagabov (Научный диалог)
Representation of the Stalingrad Battle in the British Press is examined in this study, with a focus on the coverage of events on the Volga in the regional British press. The specific portrayal of the Stalingrad Battle in the Western Post newspaper is analyzed, particularly during the defensive battles and the Soviet counteroffensive known as “Operation Uranus.” A review of all issues of the newspaper from 1942-1943 dedicated to the Stalingrad Battle is conducted. The novelty of this research lies in the introduction of a new historical source that is virtually unknown to both Russian and global readers. Typically, historiography examines materials from the central press. The relevance of this study is justified by the need to reveal a new perspective in the examination of the British press during wartime. The authors focus on how the Western Post portrayed the courage of Soviet soldiers, the professionalism of command, and the heroism of civilians in Stalingrad. It is proven that the local British press during World War II provided an overall objective picture of the battle on the Volga but paid less attention to events on the Eastern Front compared to operations in North Africa and the Mediterranean.